A problem in honour of solving 1000 problems

Is 1001 a pentagonal number?

Note: If yes, then enter the term number of 1001 in the sequence of pentagonal numbers as your answer. For example, the term number of 12 is 3, so you will enter the answer as 3; If no, then enter the answer as 1001.

Bonus question : How will you find whether a number is a pentagonal number or not? Is there any test?


The answer is 26.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

13 solutions

Salma Gamal
Apr 24, 2015

You can notice that every pentagonal number includes the privious one but you add a certan number So I wrote it as a sequence (1, 4, 7, 10...) [notice that 5=4+1 , 12=7+5] So we can concloude that any pentagonal number equals the sum off all n terms before it Using the rule sn=n/2 (2a+d (n-1)) , 1001=n/2(2+3 (n-1)), 3n^2-n-2002=0, n= 26 or n=-77/3, n=26

Nihar Mahajan
Apr 24, 2015

The simplest way to test whether a positive integer x x is a pentagonal number is :

n = 24 x + 1 + 1 6 \Large n=\dfrac{\sqrt{24x+1}+1}{6}

If n n is a natural number , then x x is the n t h n^{th} pentagonal number.

Here x = 1001 x=1001 , we get :

n = 24 ( 1001 ) + 1 + 1 6 n = 24024 + 1 + 1 6 n = 24025 + 1 6 n = 155 + 1 6 n = 156 6 n = 26 \Large {n=\dfrac{\sqrt{24(1001)+1}+1}{6} \\ \Rightarrow n=\dfrac{\sqrt{24024+1}+1}{6} \\ \Rightarrow n=\dfrac{\sqrt{24025}+1}{6} \\ \Rightarrow n=\dfrac{155+1}{6} \\ \Rightarrow n=\dfrac{156}{6}} \\ \Rightarrow \huge\boxed{n=26}

Moderator note:

This solution is incomplete. Where did you get the formula n = 24 x + 1 + 1 6 n = \frac {\sqrt{24x+1} +1}{6} ?

Here's how we get this:

Note that the series for the pentagonal numbers obeys the following recurrence:

T n + 1 T n = 4 + 3 ( n 1 ) = 1 + 3 n n 1 ; T 1 = 1 T_{n+1}-T_n=4+3(n-1)=1+3n~\forall~n\geq 1~;~T_1=1

This recurrence can be solved by "piling up the differences between terms" as follows:

T n = i = 0 n 1 ( 1 + 3 i ) = n + 3 i = 1 n ( i 1 ) = n ( 1 + 3 2 ( n 1 ) ) n 1 T_n=\sum_{i=0}^{n-1}(1+3i)=n+3\cdot\sum_{i=1}^n(i-1)=n\left(1+\frac{3}{2}(n-1)\right)~\forall~n\geq 1

Now, let x 1 x\geq 1 be a number selected for testing. We form a "testing method" using the closed form for T n T_n obtained.

T n = x 2 x = 2 n + 3 n 2 3 n = 3 n 2 n 3 n 2 n 2 x = 0 T_n=x\implies 2x=2n+3n^2-3n=3n^2-n\\ \implies 3n^2-n-2x=0

Using the quadratic formula, one gets,

n = 1 ± 1 + 24 x 6 n=\frac{1\pm \sqrt{1+24x}}{6}

But, we need value of n n to be 1 \geq 1 to test whether it is in the sequence or not and values of n n obtained that are < 1 \lt 1 are just extraneous solutions. So, our required "testing value" is,

n = 1 + 1 + 24 x 6 n=\frac{1+\sqrt{1+24x}}{6}

We have our "testing method" ready and it is now obvious from the result obtained that,

n Z + x is a pentagonal number. n\in\Bbb{Z^+}\iff~x\textrm{ is a pentagonal number.}

Prasun Biswas - 6 years, 1 month ago

Log in to reply

I Can't understand your "piling up the differences between the terms".

Vishal Yadav - 5 years, 6 months ago

Log in to reply

By "difference", I mean the f ( n ) f(n) in T n + 1 T n = f ( n ) T_{n+1}-T_n=f(n) , i.e., the variable difference between the terms. When I say "piling up the differences", I'm just saying that we sum up these variable differences up to get the closed form. Here's a simple demonstration as to how the summing method works :

We have the base cases T 0 = 0 T_0=0 and T 1 = 1 T_1=1 by definition and the following recurrence n 1 \forall~n\geq 1 :

T n + 1 T n = 1 + 3 n T n + 1 = 1 + 3 n + T n T n + 1 = ( 1 + 3 n ) + ( 1 + 3 ( n 1 ) ) + T n 1 T n + 1 = ( 1 + 3 n ) + ( 1 + 3 ( n 1 ) ) + + ( 1 + 3 ( n n ) ) + T 0 = 0 T n + 1 = i = 0 n ( 1 + 3 i ) T n = i = 0 n 1 ( 1 + 3 i ) n 1 T_{n+1}-T_n=1+3n\\ \implies T_{n+1}=1+3n+T_n\\ \implies T_{n+1}=(1+3n)+(1+3(n-1))+T_{n-1}\\ \vdots\\ \implies T_{n+1}=(1+3n)+(1+3(n-1))+\ldots+(1+3(n-n))+\underbrace{T_0}_{=0}\\ \implies T_{n+1}=\sum_{i=0}^n (1+3i)\implies T_n=\sum_{i=0}^{n-1} (1+3i)~\forall~n\geq 1

P.S - Thanks to you, I noticed a minor typo that was in my comment. Fixed it just now. :)

Prasun Biswas - 5 years, 6 months ago

It can be derived easily as the nth pentagular number is sum of first n numbers of the series 1,4,7,10...........

A Former Brilliant Member - 6 years, 1 month ago

Log in to reply

Yeah.......!

Nihar Mahajan - 6 years, 1 month ago

Yes. Simple Plug and Check :3

Mehul Arora - 6 years, 1 month ago

Log in to reply

Cheers! xD

Nihar Mahajan - 6 years, 1 month ago

Log in to reply

Yeah! Cheers! xD

Mehul Arora - 6 years, 1 month ago

Log in to reply

@Mehul Arora crap made a mistake of division. Hahahaha

A Former Brilliant Member - 6 years, 1 month ago

Log in to reply

@A Former Brilliant Member Bhai hota hai kabhi kabhi .. xD

Nihar Mahajan - 6 years, 1 month ago

This question works for me too.See my profile this was my 1000th question too .

Gautam Sharma - 6 years, 1 month ago

Log in to reply

Then , you can post another problem...

Nihar Mahajan - 6 years, 1 month ago

Log in to reply

Okay here comes mine.

Gautam Sharma - 6 years, 1 month ago
Christopher Hsu
May 16, 2015

A method my 8th grade mathcounts teacher taught me is that pentagonal, triangonal, etc. numbers can be approximated with a combination of a square and triangles.

A triangular number is n ( n 1 ) / 2 n(n-1)/2 A square is n 2 n^2

Thus a pentagonal number would be n 2 + n ( n 1 ) / 2 n^2 + n(n-1)/2 . Much easier than memorizing formulas, right?!

And n=26.

Vijay Simha
Apr 25, 2015

The Expression for the nth pentagonal number is n(3n-1)/2,

Equate n(3n-1)/2 = 1001 and this gives us the quadratic equation:

3n^2 - n - 2002 = 0

Solver for n

3n^2 - 78n + 77n - 2002 = 0

3n(n-26) + 77(n-26) = 0

(3n + 77)(n -26) = 0

The only solution permissible is n = 26

Bill Bell
Apr 24, 2015

This is a pretty easy way to do it too, provided that the number is not enormous.

Incidentally the formula used in this script and that test are both provided in wikipedia.

Ken Gene Quah
May 31, 2016

Note that 1 = 1 , 5 = 1 + 4 , 12 = 1 + 4 + 7 1 = 1, 5 = 1 + 4, 12 = 1 + 4 + 7 etc. So these numbers are in the form of 3 n 2 3n - 2 .

A sum of an arithmetic progression is the (average of the first and last number) times (number of terms)

(example 1 + 2 + 3... + 9 = ( 1 + 9 ) / 2 × 9 = 45 1+2+3...+9 = (1+9)/2 \times 9 = 45 )

This can be rearranged to form (first term + last term) times (number of terms divided by 2)

Therefore, since each term of a pentagonal number is 3 n 2 3n-2 , a pentagonal number is in the form of ( 1 + 3 n 2 ) × n 2 = (1 + 3n - 2) \times \frac {n}{2} =

= n ( 3 n 1 ) 2 =\frac {n(3n-1)}{2}

Checking, we prove by induction

Base case n = 1 n=1 : 1 × 2 2 = 1 \frac {1 \times 2}{2} = 1 . Therefore n=1 is true

the last term on the LHS is 3 n 2 3n-2 . Therefore the next term is 3 ( n + 1 ) 2 = 3 n + 1 3(n+1)-2 = 3n + 1 .

Using the inductive hypothesis, we add 3 n + 1 3n + 1 to the RHS

= n ( 3 n 1 ) 2 + 3 n + 1 =\frac {n(3n-1)}{2} + 3n + 1

= n ( 3 n 1 ) 2 + 6 n + 2 2 = 3 n 2 n + 6 n + 2 2 = 3 n 2 + 5 n + 2 2 \frac {n(3n-1)}{2} + \frac {6n+2}{2} = \frac {3n^2-n + 6n+2}{2} = \frac {3n^2+5n+2}{2}

Using Null Factor Law, n = 1 n=-1 makes this expression = 0 =0 , so we can factorise it with one of it's factors being n + 1 n+1

= ( n + 1 ) ( 3 n + 2 ) 2 = ( n + 1 ) [ 3 ( n + 1 ) 1 ] 2 \frac {(n+1)(3n+2)}{2} = \frac {(n+1)[3(n+1)-1]}{2}

Since n + 1 is true, and n = 1 is true, this formula works.

Solving,

n ( 3 n 1 ) 2 = 1001 \frac {n(3n-1)}{2} = 1001

3 n 2 n 2002 = 0 3n^2 - n - 2002 = 0

n = b ± b 2 4 a c 2 a n = \frac{-b \pm \sqrt{b^2-4ac}}{2a}

n = 1 ± 1 + 24024 6 n = \frac{1 \pm \sqrt{1+24024}}{6}

n = 1 ± 155 6 n = \frac {1 \pm 155}{6}

= 156 6 = 26 =\frac {156}{6} = \boxed{26} (The other solution 154 / 6 -154/6 is negative and not needed)

thanks for the solution. it helped me understand this problem more. :)

A Former Brilliant Member - 3 years, 5 months ago
Ador El
May 15, 2015

It can be seen that

  • term 1 -> 1+0+0
  • term 2 -> 2+1+1
  • term 3 -> 3+2+2
  • term 4 -> 4+3+3
  • term 5 -> 5+4+4
  • term 6 -> 6+5+5 So
 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
14
15
16
17
using System.IO;
using System;

class Program
{
    static void Main()
    {
        int no_points =  0;
        int counter  = 1;
        while(no_points <= 1000)
        {
            no_points += counter + ( counter - 1 ) * 2;
            Console.WriteLine(no_points + " term ->" + counter);
            counter++;
        }
    }
}

Dillon Chew
Apr 26, 2015

Pattern of 1, 5, 12, 22, 35, 51 -> Formula of sequence is (n*(3n-1))/2. Therefore, 3n^2-n-2002 = 1001, n = 26.

Alex Li
Jan 10, 2016

I did this by figuring out how much each pentagonal number increases each time. Assuming the first picture is n = 1

Every time, 3 new lines are added of size n, but because of corners, 2 are counted twice.

Therefore, we can say that n * 3 - 2 dots are added each time. (Ex. For the first case, 1 * 3 -2 = 1 dot is added to 0)

However, n* 3 - 2 is neither a geometric nor arithmetic sequence. However, by splitting it up, you can make it both. In other words, counting the total number of ns given by each part of the equation. (pretty proud of thinking of this) Now the problem becomes easy. First, the -2 term. At any n, the - 2 part of the equation will have taken 2n dots total.

For the 3x, it gets a bit more complex, because you can't just multiply by x, so instead, find the average of all terms. A good way of doing this is adding the first and last term, than dividing by 2. (3+3x)/2. Finally, multiply again by x (average * number of terms = total), and add it back to the other formula and you'll get

(3x+3x^2)/2-2x; or x(1.5x-3.5) if you like it that way.

Now it's simply a matter of plugging in integers (which is what I did) or setting it equal to 1001 and using algebra (which I guess is the 'smart' way), and you'll find that, for x = 26, y = 1001.

Jesse Nieminen
May 30, 2015

p(n) = p(n-1) + 3(n-1) + 1

=> p(n) = (3n^2 - n)/2

(3n^2 - n)/2 = 1001 (quadratic equation solved)

n = 26

x is pentagonal number if and only if

there is a positive integer n with satisfies (3n^2 - n)/2 = x

Joel Shah
May 15, 2015

The sequence proceeds as 1, 5, 12, 22, 35, between each term the differences proceed as 4, 7, 10, 13 and the difference is permanently 3, so we can deduce this must be based around square numbers. so we take 1^2 + 0 = 1, 2^2 +1 = 5, 3^2 +3 = 12, as you can see the term added is a triangle number, so the formula we use for this is ((n-1)^2+(n-1))/2 , so the formula we get for pentagonal numbers is n^2 +((n-1)^2 +(n-1))/2, which is simplified to n ( 3n -1 ) /2. Then we can form the equation n ( 3n -1 ) /2 = 1001, then you solve the equation to get n = 26

i come to two different methods to solve this: the pentagonal number of n equals either \sum {n}^2n-1­ or n^2 + \sum {i=1}^n-1

we know that any sum from 1 to any value equals half the square of n plus half the value of n, allowing us to get the formula

P= n^2 + ( (n-1)^2 + n-1) / 2

or

P=n^2 + n*(n-1)/2

therefore P= 3(n^2)/2 - n/2

Chockalingam S
Apr 30, 2015

Solved exactly like Prasun Biswas, except that I took P(n) - P(n-1) = 3n-2

P(n) be the 'n'th pentagon number then its easily noticed that P(n) = (3n-2) + P(n-1)

the difference d is 4+3(n-1) by putting this value in equation an=a1+(n-1)d the ans is 26

Raja Ghazanfar - 6 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...